The Role of Young Mothers' Coping with Parenting Stress in the Quality of their Parenting. - Raskin, Maryna. (2017)
Abstract: Adolescent parenting is a risk factor for poor parenting quality. Young mothers are exposed to multiple stressors which may decrease their capacity for sensitive caregiving. Nonetheless, there is a large degree of variability in the quality of teen mothers' parenting. Embedded in a longitudinal randomized controlled trial evaluation of a large child maltreatment prevention home visiting program, this dissertation study examined whether differences in how adolescent mothers cope with parenting stress help explain this heterogeneity in parenting outcomes. To answer this question, the author developed and validated a measure of reflective coping. The proposed factor structure of coping was evaluated using confirmatory factor analysis. The analysis did not confirm the structure of the originally proposed model of coping but a revised model fit the data well. Results confirmed the hypothesis that the negative impact of risk factors was weakened when mothers engaged in higher reflective coping. This study enhances our understanding of antecedents of positive parenting in high-risk populations and informs prevention programming and policy.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Child Development.; Advisor: M. Ann Easterbrooks.; Committee: Donald Wertlieb, Xiaodong Liu, and Sally Powers.; Keyword: Developmental psychology.